การพัฒนาโปรแกรมการตรวจสอบปริมาณรังสีในลำรังสีสำหรับงานรังสีรักษาระยะไกล: The development of dose calculation verification software in treatment field for external radiation therapy - Udee, Nuntawat (Asian Health, Science and Technology Reports, 2011)
Cancer treatment with radiation therapy is becoming widely treatment because of the external radiotherapy from high-energy linear accelerator was good treatment outcome. Therefore the high radiation dose, these should be verification of the dose calculation. This study has developed computer software to verifying radiation dose which calculated by computerized treatment planning system (TPS) prior to actual treatment. Results showed that the verification of performance of dose calculation between developed software with measured by ionization chamber (IC) and film in square and rectangular fields, the average percentage difference were -0.41 1.28 and 0.11 1.25, respectively. The comparison dose in the fields similar to the actual treatment including asymmetric and shaped fields, found that the average percentage difference between the developed software with measured were -0.16 1.07 and -0.35 1.32, respectively. The results of the tests carried out to access the percentage differences were required by International Atomic Energy Agency (IAEA).